Implementasi Dasa Dharma Ke-10 pada Siswa di Min 6 Lampung Utara - Rizka Mayasari; Vatma Rahayu Putri; Kurnia Dwi Putri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Character education is currently the most important part in the world of education. Success in educating students can be judged by how successful the student's character is. The character of students can be reflected in good personal words, good mindsets, and good deeds. With the development of the current era, it influences many changes in the character of students, such as impolite behavior and bad words. This change also occurred in students at MIN 6 North Lampung. This study aims to determine the character of students at MIN 6 North Lampung, have they implemented sacred behavior in thoughts, words and deeds listed in the 10th dasa dharma point in their daily lives. This study used a qualitative method with a sample of 300 students and teachers who were members of the MIN 6 academy in North Lampung. based on the results of the research that has been done, it is found that the application of the 10th dasa dharma is still not optimal enough, the application of good morals is only established between students and teachers, while among fellow students the behavior of students is still not good.